Bringing back the body into the mind: gestures enhance word learning in foreign language - Macedonia, Manuela (Frontiers in Psychology, 2014)
Foreign language education in the 21st century still teaches vocabulary mainly through reading and listening activities. This is due to the link between teaching practice and traditional philosophy of language, where language is considered to be an abstract phenomenon of the mind. However, a number of studies have shown that accompanying words or phrases of a foreign language with gestures leads to better memory results. In this paper, I review behavioral research on the positive effects of gestures on memory. Then I move to the factors that have been addressed as contributing to the effect, and I embed the reviewed evidence in the theoretical framework of embodiment. Finally, I argue that gestures accompanying foreign language vocabulary learning create embodied representations of those words. I conclude by advocating the use of gestures in future language education as a learning tool that enhances learning the mind.